Factors affecting the proliferation of street children in Iloilo City - Cordero, Marichelle; Ilisan, Christine Mary Aniversario; Naces, Gracenia Fortunado; Rebollos, aubrey Edlhene Estanislao; Somodio, Roma Marie Arceta
This study aims to know the factors affecting the proliferation of street children in Iloilo City. The respondents in the study are street children found in the streets of Iloilo City. This study was done through a survey among thirty-one (31) respondents. According to the findings, most of the street children were male. Moreover, poverty is the major factor that deters other problems aassociated with street children such as lack of education, dysfunctional and large families. In general, this study finds out that the different factors affecting the proliferation of street children in Iloilo city are economic, socio-cultural factors and the role of government and non-government organizations (NGOs).